Two-component ceramic tile back adhesive as well as preparation method and use method thereof

Through the use of two-component tiles, the problem of poor combination of traditional cement laying materials and large-scale finishing materials has been solved, significantly improving the bonding strength and freeze-thaw resistance, and avoiding hollowing and brick loss.

CN119569401APending Publication Date: 2025-03-07HUBEI LUBANG BUILDING MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411781195.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When traditional cement laying materials paste large vitrified bricks, microcrystalline stones and other materials, they are prone to dislodge, slip, hollowing or even brick loss due to incompatibility on the back, and the shrinkage of cement increases instability.

Method used

A two-component ceramic tile backing is provided. Component A composed of water, silicon modified polymer emulsion, silane coupling agent, etc. is mixed with components B composed of silicate cement, sulfur aluminate cement, etc. in a specific proportion. The backing is made to significantly improve the bonding power between the ceramic tile and the cement mortar.

Benefits of technology

The bonding strength between ceramic tiles and cement mortar is significantly improved, the hollowing problem is improved, and the bonding strength and freeze-thaw resistance are further enhanced by the addition of expansion agent and nano-silica aerogel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569401A_ABST
    Figure CN119569401A_ABST
Patent Text Reader

Abstract

The invention discloses a two-component ceramic tile back adhesive as well as a preparation method and a use method thereof, and belongs to the technical field of building materials. The double-component ceramic tile back adhesive is prepared by mixing the following components, the component A comprises water, a silicon modified high-molecular polymer emulsion, a silane coupling agent, an exciting agent, a defoaming agent and a thickening aid; and the component B comprises Portland cement, sulphoaluminate cement, active mineral powder, quartz sand, a thixotropic agent and a retarder. In addition, the invention also provides a preparation method of the two-component ceramic tile back adhesive. In addition, the invention also provides a use method of the two-component ceramic tile back adhesive, which comprises the following steps: adding the component B powder into the component A liquid material, then applying the uniformly stirred two-component ceramic tile back adhesive to the back of a ceramic tile, drying to obtain a first back adhesive layer, and then pasting by using cement mortar. According to the double-component ceramic tile back adhesive provided by the invention, the binding force of a ceramic tile and cement mortar can be remarkably improved under the cooperation of all the components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a two-component tile adhesive and a preparation method and a use method thereof. Background Art

[0002] As the types of tiles on the market gradually become more popular, such as vitrified tiles, microcrystalline stones, marble, and rock slabs, and their sizes are getting larger and larger, traditional cement paving materials often encounter similar incompatibility with their backs when pasting the above finishing materials, and are prone to separation, peeling, slipping, hollowing, and even falling off. The reason is that in addition to the heavy weight, extremely low water absorption, and high density of the above materials themselves, traditional cement mortar paving materials cannot use their traditional anchoring force to achieve the function of the gripper. At the same time, the inevitable shrinkage of cement itself also exacerbates the instability of the entire tile paving system.

[0003] How to improve the bonding strength between tiles and cement mortar and solve the problem of easy hollowing of tiles is a technical problem that needs to be solved by the existing technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the above technical deficiencies, provide a two-component tile adhesive and its preparation method and use method, and solve the technical problem of how to improve the bonding strength between tiles and cement mortar and solve the problem of easy hollowing of tiles in the prior art.

[0005] In order to achieve the above technical purpose, the technical solution of the present invention provides a two-component tile adhesive, which is made by mixing the following components in parts by weight:

[0006] Component A: 18-22 parts of water, 75-80 parts of silicon-modified polymer emulsion, 0.3-0.6 parts of silane coupling agent, 0.1-0.2 parts of activator, 0.1-0.3 parts of defoaming agent, 0.2-0.4 parts of thickening aid;

[0007] Component B: 35-45 parts of Portland cement, 15-20 parts of sulphoaluminate cement, 5-8 parts of active mineral powder, 8-10 parts of quartz sand, 0.2-0.4 parts of thixotropic agent, and 0.3-0.5 parts of retarder.

[0008] In any embodiment, the B component further includes 0.3-0.5 parts of a swelling agent.

[0009] In any embodiment, the B component further comprises 0.2-0.5 parts of nano-silicon dioxide aerogel.

[0010] In any embodiment, the mass ratio of the A component to the B component is 1:(2-3.2).

[0011] In any embodiment, the silicon-modified high molecular polymer emulsion is an organic silicon-modified high molecular acrylic polymer emulsion; and / or, the thixotropic agent is an organic bentonite; and / or, the thickening aid is one or more of methyl cellulose ether, carboxymethyl cellulose ether and ethyl cellulose ether; and / or, the active mineral powder is calcined kaolin; and / or, the retarder is one or both of sodium gluconate and sodium citrate.

[0012] In any embodiment, the expansion agent is one or both of a calcium sulfoaluminate expansion agent and a calcium oxide expansion agent.

[0013] In addition, the present invention also provides a method for preparing the above-mentioned two-component tile adhesive, comprising the following steps:

[0014] Preparation of component A: firstly, water and silicon-modified high molecular polymer emulsion are stirred and mixed, and then a silane coupling agent, an activator, a defoaming agent and a thickening aid are added and stirred continuously to obtain the component A;

[0015] Preparation of component B: mixing and stirring silicate cement, sulphoaluminate cement, active mineral powder, quartz sand, thixotropic agent and retarder to obtain the component B;

[0016] The two-component tile adhesive is obtained by adding component B to component A under stirring.

[0017] In addition, the present invention also provides a method for using the above two-component tile adhesive or the two-component tile adhesive prepared by the above preparation method, comprising the following steps:

[0018] Add the powder of component B to the liquid of component A while stirring and mix evenly. Then apply the evenly stirred two-component tile adhesive to the back of the tile and dry to obtain the first adhesive layer. Then use cement mortar to paste.

[0019] In any embodiment, the second adhesive layer is further coated with a two-component tile adhesive that has been stirred evenly on a part of the dried first adhesive layer, and then the second adhesive layer is pasted with cement mortar after drying.

[0020] In any embodiment, the thickness of the second adhesive layer is 0.8-1.1 mm.

[0021] Compared with the prior art, the beneficial effects of the present invention include: the two-component tile adhesive proposed in the present invention can significantly improve the bonding force between tiles and cement mortar with the cooperation of various components, and has relatively excellent bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the structure of the vitrified tile after coating the first adhesive layer and the second adhesive layer in the relevant test 2 of the present invention.

[0023] Explanation of the accompanying reference numerals: 1, vitrified tile; 2, first adhesive layer; 3, second adhesive layer; 31, second adhesive sub-layer. DETAILED DESCRIPTION

[0024] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0025] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0026] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0027] This specific embodiment provides a two-component tile adhesive, which is made by mixing the following components in parts by weight:

[0028] Component A: 18-22 parts of water, 75-80 parts of silicon-modified polymer emulsion, 0.3-0.6 parts of silane coupling agent, 0.1-0.2 parts of activator, 0.1-0.3 parts of defoaming agent, 0.2-0.4 parts of thickening aid;

[0029] Component B: 35-45 parts of Portland cement, 15-20 parts of sulphoaluminate cement, 5-8 parts of active mineral powder, 8-10 parts of quartz sand, 0.2-0.4 parts of thixotropic agent, and 0.3-0.5 parts of retarder.

[0030] In some embodiments, the silicon-modified high molecular polymer emulsion is an organic silicon-modified high molecular acrylic polymer emulsion; and / or, the thixotropic agent is organic bentonite; and / or, the thickening aid is one or more of methyl cellulose ether, carboxymethyl cellulose ether and ethyl cellulose ether; and / or, the active mineral powder is calcined kaolin; and / or, the retarder is one or both of and sodium citrate; and / or, the silane coupling agent is KH560 silane coupling agent; and / or, the defoamer is an organic silicon defoamer, and in some embodiments, BYK-024 is used; and / or, the activator is triethanolamine.

[0031] The above solution can significantly improve the bonding strength between tiles and cement mortar and improve the problem of hollowing. However, due to the shrinkage stress during the drying process of the tile adhesive, the bonding strength between the tile adhesive and the tiles is poor.

[0032] Based on this consideration, we choose to add an expansion agent. Specifically, in some embodiments, the B component also includes 0.3-0.5 parts of an expansion agent. In some embodiments, the expansion agent is one or both of a calcium sulfoaluminate expansion agent and a calcium oxide expansion agent. The addition of the expansion agent can cause the tile adhesive to expand slightly and offset the shrinkage stress generated by the drying shrinkage of the tile back layer, which only improves the adhesion strength of the tile adhesive to the tile to a small extent, which does not meet our expectations.

[0033] As for the reason, we further studied and found that it is likely that the expansion agent produced pores during the expansion process. The production of pores weakened the bonding strength between the tile backing adhesive and the tile. Based on this, we considered adding nano-silica aerogel, specifically, adding 0.2-0.5 parts of nano-silica aerogel to component B.

[0034] The nano-silica aerogel has a certain flexibility after coming into contact with water and can fill the pores produced by the expansion of the expansion agent. In the subsequent drying process, although the nano-silica aerogel will lose water, the volume of the dried nano-silica aerogel hardly changes and can always fill the pores. Moreover, the dried nano-silica aerogel has a certain strength, thereby strengthening the bonding strength between the tile adhesive and the tile, and thus significantly improving the bonding strength of the tile adhesive to the tile.

[0035] In addition, this specific embodiment also proposes a method for preparing the above-mentioned two-component tile adhesive, comprising the following steps:

[0036] Preparation of component A: firstly, water and silicon-modified high molecular polymer emulsion are stirred and mixed, and then a silane coupling agent, an activator, a defoaming agent and a thickening aid are added and stirred continuously to obtain the component A;

[0037] Preparation of component B: mixing and stirring silicate cement, sulphoaluminate cement, active mineral powder, quartz sand, thixotropic agent and retarder to obtain the component B;

[0038] The two-component tile adhesive is obtained by adding component B to component A under stirring.

[0039] In some embodiments, if a swelling agent and / or nano-silica aerogel is added, it can be mixed and stirred together with other components in component B.

[0040] In addition, this specific embodiment also proposes a method for using the above-mentioned two-component tile adhesive or the two-component tile adhesive prepared by the preparation method of the above-mentioned two-component tile adhesive, comprising the following steps:

[0041] Add the powder of component B to the liquid of component A while stirring and mix evenly. Then apply the evenly stirred two-component tile adhesive to the back of the tile and dry to obtain the first adhesive layer. Then use cement mortar to paste.

[0042] In order to make the tile adhesive and cement mortar fit more firmly, we considered further applying the two-component tile adhesive on the dried first adhesive layer to obtain a second adhesive layer, and then using cement mortar for pasting after drying. The thickness of the second adhesive layer is 0.8-1.1mm. The second adhesive layer distributed on the local surface of the first adhesive layer is slightly raised, which increases the contact area with the cement mortar. The concave and convex matching of the structure is similar to the effect of embedding, which makes the two more closely combined, thereby improving the bonding strength.

[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0044] In the present invention, reference is made to “some embodiments”, “this embodiment”, examples, etc., which describe a subset of all possible embodiments, but it can be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.

[0045] If similar descriptions of "first / second" appear in the application documents, the following instructions are added. In the following description, the terms "first\second\third" involved are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It can be understood that "first\second\third" can be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein.

[0046] In this embodiment, the term "and / or" is merely a description of the association relationship between associated objects, indicating that three relationships may exist. For example, object A and / or object B may represent three situations: object A exists alone, object A and object B exist at the same time, and object B exists alone.

[0047] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0048] It should be noted that the activator in the following embodiments is triethanolamine, the silane coupling agent is KH560 silane coupling agent, the defoamer is BYK-024, the thixotropic agent is organic bentonite, the silicon-modified polymer emulsion is an organic silicon-modified polymer acrylic polymer emulsion, and the active mineral powder is calcined kaolin. The raw materials used in this application are all from the prior art. For example, the organic silicon-modified polymer acrylic polymer emulsion uses K-18 from Jiangsu Gezhi Materials Co., Ltd.

[0049] Example 1

[0050] This embodiment provides a two-component tile adhesive, which is made by mixing the following components in parts by weight:

[0051] Component A: 18 parts of water, 75 parts of organosilicon-modified high molecular acrylic polymer, 0.3 parts of silane coupling agent, 0.1 parts of activator, 0.2 parts of defoaming agent, and 0.2 parts of thickening aid methyl cellulose ether;

[0052] Component B: 40 parts of Portland cement, 15 parts of sulphoaluminate cement, 8 parts of active mineral powder, 8 parts of quartz sand, 0.3 parts of thixotropic agent, and 0.3 parts of retarder sodium gluconate.

[0053] This embodiment also provides a method for preparing the above-mentioned two-component tile adhesive, comprising the following steps:

[0054] Preparation of component A: firstly, water and silicone-modified high molecular acrylic polymer are stirred and mixed, and then a silane coupling agent, an activator, a defoaming agent and a thickening aid methyl cellulose ether are added and stirred continuously to obtain the component A;

[0055] Preparation of component B: mixing and stirring silicate cement, sulphoaluminate cement, active mineral powder, quartz sand, thixotropic agent and retarder sodium gluconate to obtain the component B;

[0056] The two-component tile adhesive is obtained by adding component B to component A under stirring.

[0057] Example 2

[0058] This embodiment provides a two-component tile adhesive, which is made by mixing the following components in parts by weight:

[0059] Component A: 19 parts of water, 78 parts of organosilicon-modified high molecular acrylic polymer, 0.5 parts of silane coupling agent, 0.1 parts of activator, 0.2 parts of defoaming agent, 0.3 parts of thickening aid carboxymethyl cellulose ether;

[0060] Component B: 35 parts of Portland cement, 18 parts of sulphoaluminate cement, 6 parts of active mineral powder, 10 parts of quartz sand, 0.3 parts of thixotropic agent, and 0.4 parts of retarder sodium citrate.

[0061] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0062] Example 3

[0063] This embodiment provides a two-component tile adhesive, which is made by mixing the following components in parts by weight:

[0064] Component A: 22 parts of water, 80 parts of organic silicon modified high molecular acrylic polymer, 0.4 parts of silane coupling agent, 0.2 parts of activator, 0.1 parts of defoaming agent, 0.4 parts of thickening aid ethyl cellulose ether;

[0065] Component B: 45 parts of Portland cement, 16 parts of sulphoaluminate cement, 7 parts of active mineral powder, 9 parts of quartz sand, 0.2 parts of thixotropic agent, and 0.3 parts of retarder sodium citrate.

[0066] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0067] Example 4

[0068] This embodiment provides a two-component tile adhesive, which is made by mixing the following components in parts by weight: sodium gluconate

[0069] Component A: 20 parts of water, 76 parts of organosilicon-modified high molecular acrylic polymer, 0.6 parts of silane coupling agent, 0.2 parts of activator, 0.3 parts of defoaming agent, 0.4 parts of thickening aid ethyl cellulose ether;

[0070] Component B: 43 parts of silicate cement, 20 parts of sulphoaluminate cement, 5 parts of active mineral powder, 8 parts of quartz sand, 0.4 parts of thixotropic agent, and 0.5 parts of retarder ethyl cellulose ether.

[0071] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0072] Example 5

[0073] The two-component tile adhesive of this embodiment is different from that of Embodiment 1 only in that component B also includes 0.4 parts of calcium sulfoaluminate expansion agent.

[0074] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0075] Example 6

[0076] The two-component tile adhesive of this embodiment is different from that of Embodiment 2 only in that component B also includes 0.3 parts of calcium sulfoaluminate expansion agent.

[0077] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0078] Example 7

[0079] The two-component tile adhesive of this embodiment is different from that of Embodiment 3 only in that component B also includes 0.5 parts of calcium oxide expansion agent.

[0080] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0081] Example 8

[0082] The two-component tile adhesive of this embodiment is different from that of Embodiment 5 only in that component B also includes 0.3 parts of nano-silicon dioxide aerogel.

[0083] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0084] Example 9

[0085] The two-component tile adhesive of this embodiment is different from that of Embodiment 6 only in that component B also includes 0.5 parts of nano-silicon dioxide aerogel.

[0086] The preparation method of the two-component tile adhesive in this embodiment is the same as that in Embodiment 1.

[0087] The following tests used vitrified tiles of 600mm*600mm.

[0088] Related test 1

[0089] The two-component tile adhesive prepared in Examples 1-9 was applied to the back of the vitrified tile by roller coating, and then dried at room temperature (25°C) for 24 hours before pasting with cement mortar. The tile was maintained for 28 days under standard conditions and tested according to JG / T247-2017 standard. The results are shown in Table 1.

[0090] It can be seen from Table 1 that the two-component ceramic adhesives of Examples 1-9 all have good bonding strength, especially the two-component ceramic adhesives of Examples 8-9 have a bonding strength of more than 2 Pa, and retain a relatively high bonding strength after thermal aging and freeze-thaw cycles.

[0091] Table 1 Bond strength test results of Examples 1-9

[0092]

[0093] Related test 2

[0094] The two-component tile adhesive prepared in Examples 6-9 is applied to the back of the vitrified tile by roller coating. After drying at room temperature for 24 hours, a first adhesive layer is obtained. The two-component tile adhesive is further coated and stirred on the surface of the first adhesive layer to obtain a second adhesive layer. After drying, cement mortar is used for pasting. The thickness of the second adhesive layer is 0.8-1.1 mm. Cement mortar is then used for pasting. The test was carried out according to JG / T247-2017 standard under standard conditions for 28 days. The results are shown in Table 2. The second adhesive layer is equivalent to multiple second adhesive sub-layers. The area of ​​the second adhesive sub-layer is about 50 mm*50 mm, and the spacing between adjacent second adhesive sub-layers is 100 mm*100 mm. The structure of the vitrified tile after coating with the two-component tile adhesive is as shown in the figure. Figure 1 As shown, it includes a vitrified tile 1, a first back glue layer 2 and a second back glue layer 3. The first back glue layer 2 is coated on the surface of the vitrified tile 1, and the second back glue layer 3 is coated on the surface of the first back glue layer 2. The second back glue layer 3 includes a plurality of second back glue sub-layers 31, and there is a spacing between adjacent second back glue sub-layers 31.

[0095] Table 2 Tensile bond strength and tensile bond strength after freeze-thaw cycles measured in accordance with the relevant test 2 for Examples 6-9

[0096]

[0097] It can be seen from Table 2 that by changing the coating method of the ceramic backing adhesive, the structural stability of the coating is improved, thereby showing excellent anti-freeze-thaw performance; the tensile bonding strength is also significantly improved.

[0098] We have designed a product that can not only improve the complexity of difficult-to-lay finishing materials such as vitrified tiles, but also combine with subsequent adhesive materials for high performance. Different from traditional pure liquid adhesive products on the market, it can completely solve the problem of tile laying. At the same time, the material is easy to construct, safe and reliable, and has long-lasting functions.

[0099] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A two-component tile adhesive, characterized in that: It is prepared by mixing the following components in parts by weight; Component A: 18-22 parts of water, 75-80 parts of silicon-modified polymer emulsion, 0.3-0.6 parts of silane coupling agent, 0.1-0.2 parts of activator, 0.1-0.3 parts of defoaming agent, 0.2-0.4 parts of thickening aid; Component B: 35-45 parts of Portland cement, 15-20 parts of sulphoaluminate cement, 5-8 parts of active mineral powder, 8-10 parts of quartz sand, 0.2-0.4 parts of thixotropic agent, and 0.3-0.5 parts of retarder.

2. The two-component tile adhesive according to claim 1, characterized in that: The B component also includes 0.3-0.5 parts of a swelling agent.

3. The two-component tile adhesive according to claim 2, characterized in that: The B component also includes 0.2-0.5 parts of nano-silicon dioxide aerogel.

4. The two-component tile adhesive according to any one of claims 1 to 3, characterized in that: The mass ratio of the A component to the B component is 1:(2-3.2).

5. The two-component tile adhesive according to claim 1, characterized in that: The silicon-modified high molecular polymer emulsion is an organic silicon-modified high molecular acrylic polymer emulsion; and / or, the thixotropic agent is organic bentonite; and / or, the thickening aid is one or more of methyl cellulose ether, carboxymethyl cellulose ether and ethyl cellulose ether; and / or, the active mineral powder is calcined kaolin; and / or, the retarder is one or both of sodium gluconate and sodium citrate.

6. The two-component tile adhesive according to claim 2, characterized in that: The expansion agent is one or both of a calcium sulfoaluminate expansion agent and a calcium oxide expansion agent.

7. A method for preparing the two-component tile adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: Preparation of component A: firstly, water and silicon-modified high molecular polymer emulsion are stirred and mixed, and then a silane coupling agent, an activator, a defoaming agent and a thickening aid are added and stirred continuously to obtain the component A; Preparation of component B: mixing and stirring silicate cement, sulphoaluminate cement, active mineral powder, quartz sand, thixotropic agent and retarder to obtain the component B; The two-component tile adhesive is obtained by adding component B to component A under stirring.

8. A method for using the two-component tile adhesive as claimed in any one of claims 1 to 6 or the two-component tile adhesive prepared by the preparation method of the two-component tile adhesive as claimed in claim 7, characterized in that: The following steps are involved: Add the powder of component B to the liquid of component A while stirring and mix evenly. Then apply the evenly stirred two-component tile adhesive to the back of the tile and dry to obtain the first adhesive layer. Then use cement mortar to paste.

9. The method of use according to claim 8, characterized in that: The method also includes further coating the evenly stirred two-component tile adhesive on a part of the dried first adhesive layer to obtain a second adhesive layer, and pasting the second adhesive layer with cement mortar after drying.

10. The method of use according to claim 9, characterized in that: The thickness of the second adhesive layer is 0.8-1.1 mm.

Citation Information

Patent Citations

  • Double-component ceramic tile interface agent as well as preparation method and using method thereof

    CN103496922A

  • Nano-aerogel modified bi-component ceramic tile backing adhesive as well preparation method and use method thereof

    CN109517541A

  • Adhesive for wall tiling, preparation method of adhesive and wall tiling method adopting adhesive

    CN112608078A

  • Two-component ceramic tile back adhesive and preparation method thereof

    CN116120019A

  • Quick-hardening and high-strength two-component ceramic tile back adhesive

    CN117164316A